2021
DOI: 10.1080/1828051x.2021.1966845
|View full text |Cite
|
Sign up to set email alerts
|

Palygorskite combined probiotics improve the laying performance, hatching performance, egg quality, plasma antioxidative status, and immune response of broiler breeders

Abstract: This experiment was conducted to investigate the effects of different supplementation levels of palygorskite and probiotics complex (Pal-Pro) on laying performance, hatching performance, egg quality, plasma antioxidative status, and immune response of broiler breeders. A total of 432 Xuefeng black-bone chickens (42-week-old) were randomly assigned into four treatments with six replicates of 18 hens. The broiler breeders were fed the basal diet supplemented with 0, 250, 500, and 750 mg/kg Pal-Pro for 8 weeks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The improvement could be adducible to better nutrient utilization orchestrated by a decrease in stress response, enhanced gut health, and improved immune function, as observed in this study. This claim is supported by previous studies in laying hens, which demonstrated that probiotic-induced improvement in physiological indices, including immunity index, intestinal morphology, and antioxidant capacity culminated in significantly increased laying performance ( Deng et al, 2021 ; Wang Y. et al, 2021 ; Pan et al, 2022 ). However, some studies found no probiotic-induced effect on egg production ( Shi et al, 2020 ; Wang J. et al, 2021 ; Ray et al, 2022 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The improvement could be adducible to better nutrient utilization orchestrated by a decrease in stress response, enhanced gut health, and improved immune function, as observed in this study. This claim is supported by previous studies in laying hens, which demonstrated that probiotic-induced improvement in physiological indices, including immunity index, intestinal morphology, and antioxidant capacity culminated in significantly increased laying performance ( Deng et al, 2021 ; Wang Y. et al, 2021 ; Pan et al, 2022 ). However, some studies found no probiotic-induced effect on egg production ( Shi et al, 2020 ; Wang J. et al, 2021 ; Ray et al, 2022 ).…”
Section: Discussionsupporting
confidence: 77%
“…The immunity index of animals is often measured based on the serum concentrations of immunoglobulins (IgM, IgA, and IgG) due to their key role in immune regulation and disease resistance ( Mountzouris et al, 2010 ). Previous reports demonstrated that B. amyloliquefaciens significantly increased serum concentrations of IgG and IgA ( Ahmat et al, 2021 ) and the probiotic complex ( Deng et al, 2021 ), and B. subtilis ( Qiu et al, 2021 ) enhanced the serum immunoglobulins of IgG, IgA, and IgM in broiler birds. There are pieces of evidence that B. amyloliquefaciens increased IgG and IgA levels ( Zhou et al, 2020 ) and CB enhanced IgA, IgY, and IgM ( Zhan et al, 2019 ) in laying hens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probiotics may present improvement of antioxidant capacity, gut integrity, and immunity function as mechanisms that boost process of egg formation and albumen synthesis in laying hens. However, there are other evidences that probiotics had no significant effect on albumen quality (98,(101)(102)(103)(104). These variations among studies may be due to probiotics constituents, dosage level and physiological status of the birds.…”
Section: Probiotics and Prebioticsmentioning
confidence: 99%
“…Over an extended period of domestication, it has developed stable genetic traits and unique flavor. These traits encompass notable black features in the skin, bones, meat, beak, legs, cockscomb, and tongue ( Deng et al, 2021 ; Deng et al, 2022 ). However, a noteworthy phenomenon was observed during the slaughter process, revealing significant variations in the blackness of breast muscles ( BBM ) among Xuefeng black-bone chickens.…”
Section: Introductionmentioning
confidence: 99%